2006
DOI: 10.2217/17435889.1.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Explosion of Gold Nanoparticles: Potential Role for Nanophotothermolysis of Cancer

Abstract: Explosion of nanoparticles may be accompanied by optical plasma, generation of shock waves with supersonic expansion and particle fragmentation with fragments of high kinetic energy, all of which can contribute to the killing of cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
182
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(185 citation statements)
references
References 49 publications
0
182
0
3
Order By: Relevance
“…Among various synthesis methods, plant-mediated synthesis is preferred due to its cost effectiveness and environment-friendly nature [3,4]. GNP have applications in therapeutic [5], catalysis [2], immunoassay and immunosensing [6], diagnostic and drug delivery [7][8][9][10], analyte sensing [11][12][13], cancer cell diagnostics and selective photothermal therapy [14,15], photoacoustic imaging [16,17] and cancer treatment [18]. Various plant extracts have been explored for the synthesis of GNP, namely tamarind [19], Aloe vera [20], Pelargonium graveolens [21], Diopyros kaki [22], Eucalyptus camaldulensis and Pelargonium roseum [23], coriander [24], Scutellaria barbata [25], lemongrass [26], Datura metel, Carica papaya and Solanum melongena [27].…”
Section: Introductionmentioning
confidence: 99%
“…Among various synthesis methods, plant-mediated synthesis is preferred due to its cost effectiveness and environment-friendly nature [3,4]. GNP have applications in therapeutic [5], catalysis [2], immunoassay and immunosensing [6], diagnostic and drug delivery [7][8][9][10], analyte sensing [11][12][13], cancer cell diagnostics and selective photothermal therapy [14,15], photoacoustic imaging [16,17] and cancer treatment [18]. Various plant extracts have been explored for the synthesis of GNP, namely tamarind [19], Aloe vera [20], Pelargonium graveolens [21], Diopyros kaki [22], Eucalyptus camaldulensis and Pelargonium roseum [23], coriander [24], Scutellaria barbata [25], lemongrass [26], Datura metel, Carica papaya and Solanum melongena [27].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, use of short laser pulses, compared to continuous wave irradiation, allows less time for heat diffusion to surrounding host tissue during exposure for more localized bacterial damage and reduced nonspecific damage to normal tissue; this may also allow integration of detection through photoacoustic or other mechanisms into the treatment platform. 8,10,19 Using this approach, one research group reported a 95% killing of a methicillin-sensitive strain of S. aureus, in vitro, using laser pulses at 532 nm and a two-step nanoparticle targeting strategy involving binding of primary antibodies to the bacteria followed by treatment with secondary antibodies conjugated with gold nanospheres. 10 The purpose of the current study was to test the antibacterial effect of this laser-induced photothermal technique against both methicillin-sensitive and methicillinresistant S. aureus using a simplified, one-step method for targeting of the GNPs to the bacteria.…”
mentioning
confidence: 99%
“…Previous work studying the effect of pulsed laser on nanoparticles showed that exposure to irradiation resulted in fragmentation of particles and the generation of new extinction peaks associated with the new population [161,169,[171][172][173]. In this work, particles with diameters ranging from 20 to 50 nm with SPRs ranging from 550 to 750 nm were subjected to NIR pulsed light for 10 min at two different powers (350 and 700 J) [170].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 98%
“…It has been reported that additional time for electron-phonon relaxation is created between lapses in pulses, which leads to better heat generation [167]. This is attributed to competition between the cooling of the lattice and the rate of the nanoparticle absorption of light [169]. In contrast, the application of a CW laser is believed to dissipate absorbed energy into its environment as the temperature of the nanoparticle increases due a relatively stable thermal relationship between the nanoparticles and solvent [99,164,165].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 99%